An atypical Klippel-Treanunay-Weber syndrome - Muammer Bilir; Cuneyt Tetikkurt; Halil Yanardag (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2018)
A 44 year old female was referred for hyperbaric oxygen treatment of leg ulcers. The patient had port-wine stain, hand vitiligo, hypertrophy of one extremity, collateral abdominal, and varicose leg veins. Calcium was 12 mg/dL and PTH was 309 ng/L. Hepatomegaly, deep vein thrombosis of the right leg, transudative ascites, hypersplenism, parathyroid adenoma, mesenteric cyst, and papillary thyroid carcinoma were identifi ed. The fi nal clinical diagnosis was Klippel-Treanunay-Weber syndrome. Several theories such as intrauterine damage to sympathetic ganglia, deep vein abnormalities, mesodermal and ectodermal dysplasia exist for the pathogenesis of this syndrome. This is the fi rst case of Klipel-Treanunay -Weber syndrome with coexisting vitiligo, hypersplenism, non-chirrotic hepatic fi brosis, a mesenteric cyst, a parathyroid adenoma, and a papillary thyroid carcinoma. The vitiligo, mesenteric cyst, parathyroid adenoma, and the papillary thyroid carcinoma are associated with the genetic abnormalities of the syndrome while hypersplenism and hepatic fi brosis are the late complications the disease.